Investigation of the AFM Indenter’s Geometry Effect On Micro/Nano Biological Cells’ Indentation - Yousef Habibi Sooha; Moharam Habibnejad; Zahra Rastegar (International Journal of Advanced Design and Manufacturing Technology, 2020)
The elasticity modules of the micro/Nanoparticles, especially biological particles are measured using different tools such as atomic force microscopy. The tip of the atomic force microscopy as an indenter has different shapes such as spherical, conical and pyramidal. In the contact of these tips and biological cells, avoiding the cell damage is a necessity. The goal of this paper is investigation and comparison of different tips’ geometries. Different tip’s geometries and their related theories were collected and proposed. To generalize theories’ application for any kind of particle (even non-biological particles) some of simplifying assumptions used in these theories, such as tip rigidity, were removed. Simulation of the force- indentation depth was done for gold nanoparticle and observed that if simplifying assumptions were not removed there would be big errors in calculating the elasticity module of some particles. Then, simulations were done for two yeast and mouse embryo cells. For both cells, in general, the geometry of the curve group, the geometry of the pyramidal group and finally the geometry of the conical group were positioned from the highest to the lowest places. For hyperbolic, conical and pyramidal tips, the important parameter was semi vertical angel. To observe its effect, different magnitudes of this parameter were simulated. According to observed results in three investigated geometries and for both cells, bigger semi vertical angel created higher curves and this means in bigger angels the possibility of cell damage is higher.